Comparison of Robot-Assisted, Laparoscopic, and Open Radical Prostatectomy Outcomes: A Systematic Review and Network Meta-Analysis from KSER Update Series - Do Kyung Kim; Young Joon Moon; Doo Yong Chung; Hae Do Jung; Seung Hyun Jeon; Seok Ho Kang; Sunghyun Paick; Joo Yong Lee (Medicina)
Background and Objectives: We conducted a systematic review and network meta-analysis to evaluate and compare the perioperative, functional, and oncological outcomes of robot-assisted radical prostatectomy (RARP) and laparoscopic radical prostatectomy (LRP) with open radical prostatectomy (ORP) in patients with prostate cancer. Materials and Methods: A comprehensive literature search was performed in Pubmed, EMBASE, and the Cochrane library for papers published before May 2021. Only studies of patients with prostate cancer that assessed perioperative, functional, and oncological outcomes and reported outcome values were included. We used a Bayesian hierarchical random-effects model to synthesize data from multiple studies, enabling both direct and indirect comparisons of the three surgical approaches (RARP, LRP, ORP) to provide robust estimates of their relative efficacy. This systematic review was registered in PROSPERO (CRD42021282555). Results: A total of 80 studies were finally included in the present study. Biochemical recurrence (BCR) rates were lower for RARP than for ORP (RR 0.713, 95% CrI 0.587–0.869) and LRP (RR 0.672, 95% CrI 0.505–0.895). Compared with ORP, RARP had a significantly lower positive surgical margin (RR 0.893, 95% CrI 0.807–0.985). When compared to ORP, RARP and LRP showed no significant difference in continence (RR 1.057, 95% CrI 0.997–1.124; RR 0.921, 95% CrI 0.845–1.007). When compared to ORP, RARP was significantly more effective on potency (RR 1.201, 95% CrI 1.047–1.402). The potency rate was significantly higher for RARP than for ORP (RR 1.201, 95% CrI 1.047–1.402) and LRP (RR 1.438, 95% CrI 1.191–1.762). There was no difference in the estimated blood loss or the total and major complication rates between RARP, ORP, and LRP. The operation time was longest for LRP. There was no difference in the operation time between RARP and ORP. Conclusions: RARP may be better or comparable to ORP and LRP in terms of oncologic outcomes (PSM and BCR), functional outcomes (potency and incontinence), and perioperative outcomes (EBL, operation time, and total and major complications).